Trends in sexually transmitted infections (other than HIV) in older people: analysis of data from an enhanced surveillance system. Issue 4 (27th June 2008) - Bodley-Tickell, A T; Olowokure, B; Bhaduri, S; White, D J; Ward, D; Ross, J D C; Smith, G; Duggal, H V; Goold, P
Abstract : Objective: This study examines the distribution of selected sexually transmitted infections (STIs) in older people (aged ⩾45 years) attending genitourinary medicine (GUM) clinics in the West Midlands, UK. Methods: Analysis of data from the regional enhanced STI surveillance system for the period 1996–2003. Selected STIs were chlamydia, genital herpes, genital warts, gonorrhoea and syphilis. Results: Altogether, 4445 STI episodes were reported among older people during the study period. Between 1996 and 2003 older people accounted for 3.7% and 4.3%, respectively, of all GUM clinic attendances. The rate of STIs in older people more than doubled in 2003 compared with 1996 (p<0.0001). Rates for all five selected diagnoses were significantly higher in 2003 compared to 1996. A significantly increasing trend over time was seen overall (p<0.0001) and for each of the selected diagnoses. Overall, males and those aged 55–59 years of age were significantly more likely to be affected. Conclusions: This study provides evidence of significant increases in attendance at GUM clinics by older people. Although it is recognised that young people should remain the focus of sexual health programmes, the results indicate that sexual risk-taking behaviour is not confined to young people but also occurs among older people. There is therefore a need to develop and implement evidence-based multifaceted sexual health programmes that while aiming to reduce STI transmission among all age groups should include interventions aimed specifically at older people and address societal and healthcare attitudes, myths and assumptions about sexual activity among older people.